2014
DOI: 10.1111/jcpe.12299
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline microbiological status on clinical outcomes in generalized aggressive periodontitis patients treated with or without adjunctive amoxicillin and metronidazole: an exploratory analysis from a randomized controlled clinical trial

Abstract: All subjects benefited from the tested adjunctive antimicrobial regimen, although subjects who harboured A. actinomycetemcomitans at baseline may show greater clinical benefits. Larger appropriately powered studies are needed to confirm whether adjunctive AMX-MET is more beneficial for GAgP patients who harbour A. actinomycetemcomitans, along with other key periodontal pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
55
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(62 citation statements)
references
References 45 publications
5
55
2
Order By: Relevance
“…When baseline subgingival microbial data were considered, Ardila and co‐workers (using moxifloxacin as adjunct) reported differences favouring the antibiotic group in A. actinomycetemcomitans +ve versus A. actinomycetemcomitans −ve for PPDs ≥ 7 mm (1.96 mm vs. 1.14 mm, respectively) and for PPDs 4–6 mm (0.92 mm vs. 0.51 mm, respectively) (Ardila & Guzman, ). Similarly, Guerrero and co‐workers reported that the percentage of sites changing from ≥5 mm to ≤4 mm PPDs at 6 months was 80.9% for A. actinomycetemcomitans +ve individuals treated with adjunctive antibiotics, compared to 71.1% for A. actinomycetemcomitans −ve individuals treated with adjunctive antibiotics (Guerrero et al, ). In contrast, when no antibiotics were prescribed, the change from ≥5 mm to ≤4 mm PPDs was found to be 52.6% for A. actinomycetemcomitans +ve and 60.9% for A. actinomycetemcomitans −ve individuals.…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…When baseline subgingival microbial data were considered, Ardila and co‐workers (using moxifloxacin as adjunct) reported differences favouring the antibiotic group in A. actinomycetemcomitans +ve versus A. actinomycetemcomitans −ve for PPDs ≥ 7 mm (1.96 mm vs. 1.14 mm, respectively) and for PPDs 4–6 mm (0.92 mm vs. 0.51 mm, respectively) (Ardila & Guzman, ). Similarly, Guerrero and co‐workers reported that the percentage of sites changing from ≥5 mm to ≤4 mm PPDs at 6 months was 80.9% for A. actinomycetemcomitans +ve individuals treated with adjunctive antibiotics, compared to 71.1% for A. actinomycetemcomitans −ve individuals treated with adjunctive antibiotics (Guerrero et al, ). In contrast, when no antibiotics were prescribed, the change from ≥5 mm to ≤4 mm PPDs was found to be 52.6% for A. actinomycetemcomitans +ve and 60.9% for A. actinomycetemcomitans −ve individuals.…”
Section: Resultsmentioning
confidence: 92%
“…In contrast, when no antibiotics were prescribed, the change from ≥5 mm to ≤4 mm PPDs was found to be 52.6% for A. actinomycetemcomitans +ve and 60.9% for A. actinomycetemcomitans −ve individuals. Overall, both Guerrero and co‐workers and Ardila and co‐workers suggested that all patients benefitted from the antibiotic adjunct, although its clinical effect seemed to be more pronounced (but not statistically significant) in A. actinomycetemcomitans +ve patients (Ardila & Guzman, ; Guerrero et al, ). On the contrary, Cionca and co‐workers concluded that the adjunctive clinical benefits attributable to the antibiotic were obtained regardless of the baseline presence or absence of the six studied periodontal pathogens (Cionca et al, ).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations